Peningkatan Keterampilan Tendangan Dalam Pencak Silat Melalui Variasi Gerak Dasar Tendangan “T” dan Tendangan Depan Pada Siswa Kelas V SDN Pinggir Papas 1 - Amroin, Yoni Sakti; Indahwati, Nanik (Lembaga Penelitian dan Pendidikan Mandala, 2021)
The purpose of this study was to improve the learning outcomes of basic kick motion skills in pencak silat through variations of the basic 'T' and front kick motion using assistive media in fifth grade students of SDN Pinggir Papas I in the 2020/2021 academic year.This research was a Classroom Action Research (PTK). The research was carried out using one cycle, if the desired results have not been achieved then the following cycle is continued, with each cycle consisting of planning, implementing actions, observing and reflecting. The subjects of this study were twenty-four students of grade five SDN Pinggir Papas I for the 2020/2021 academic year. The data sources came from teachers and students. Data collection by front kick pencak silat and activity observation during the teaching and learning activities of kicks in pencak silat using learning aids. The data in this study were in the form of quantitative and qualitative data. In this research, it produces data on the improvement of students in learning the basic movements of the T kick and front of the pencak silat with variations and learning aids. The achievement of completeness of the learning outcomes of the pencak silat T kick from pre-cycle one is about sixty-seven percent. From cycle one to cycle two amounted to twenty five percent. Meanwhile, learning outcomes for front kicks from pre-cycle to cycle 1 experienced an increase of fifty-four percent.The improvement of learning outcomes for T and forwards kicks with variations in T and forwards kick exercises has increased until it reaches the learning target, namely reaching the good and very good categories. Based on the results of the study, the conclusion is: Variations in the basic motion of the 'T' kick and forwards in learning can improve learning outcomes of the basic movement skills of pencak silat kicks in fifth grade students of SDN Piggir Papas I in the 2020/2021 school year.